Students' perceptions of listening learning using the bottom-up strategy - sukma - irawan (Institut Agama Islam Negeri Palopo, 2021)
Listening learning using a bottom-up strategy provides a positive perception for students. The lack of research on students' perceptions of the bottom-up strategy in listening learning is the purpose of this research. The perceptions explored focused on student interest, student motivation, learning effects, problems faced, and solutions to problems students faced. The benefit of this research is to become a reference for the implementation of listening learning using a bottom-up strategy. This study uses a descriptive qualitative method with in-depth interviews with 4 students who have been learning listening using a bottom-up strategy for 2 years. The results of the interviews were analyzed using the Colaizzi method. The themes that emerged from this research were students felt this strategy was interesting, students felt this strategy was motivating in learning listening, students felt this strategy could improve their English skills apart from listening, but students felt that this strategy still had problems such as unclear sound. Students said that the problem could be fixed by making the class conducive and improving the quality of the audio that would be used.